A myeloperoxidase-responsive and biodegradable luminescent material for real-time imaging of inflammatory diseases. Issue 9 (November 2017) - Guo, Jiawei; Tao, Hui; Dou, Yin; Li, Lanlan; Xu, Xiaoqiu; Zhang, Qixiong; Cheng, Juan; Han, Songling; Huang, Jun; Li, Xiaodong; Li, Xiaohui; Zhang, Jianxiang
Graphical abstract: Abstract: We report the synthesis and characterization of a myeloperoxidase (MPO)-responsive, biodegradable, and luminescent material derived from functionalized cyclodextrin. The nanoparticle based on this functional material shows notably high and sustainable luminescent signals upon triggering by inflammatory conditions with abnormally elevated reactive oxygen species and MPO. Activated neutrophils during inflammatory responses can be selectively imaged using this nanoprobe, with luminescent signals positively correlated to neutrophil counts. This nanoprobe enables in vivo precise quantification and tracking of the number and dynamics of neutrophils in both superficial and deep tissues in various mouse models of inflammatory diseases, including peritonitis, paw edema, colitis, and acute lung injury. In vitro and in vivo evaluations also demonstrate the safety and biocompatibility of this newly engineered material in its native and nanoparticle forms.